Power Supply Security Enhancement for Active Low Voltage Power Distribution Systems Based on Topological Reconfiguration - Zhao, Zhixuan; Liu, Jiawei; Hong, Haisheng; Yang, Kangyi; Tang, Xian; Hou, Yi (Proceedings (International Confernce on Computational Intelligence and Communication Networks), 2024)
As an important component of the power system, the low-voltage distribution network plays a crucial role in ensuring user electricity demand, promoting energy transformation, and facilitating economic development. This paper proposes a fault recovery and reconstruction method and algorithm design for active distribution networks with a large number of intermittent distributed renewable power sources and conducts simulations using a 69-node example. The proposed implementation method has been assessed through extensive simulation experiments and the numerical results confirmed the effectiveness of the proposed solution. By optimizing the structure of the power grid, strengthening equipment maintenance and management, and other measures, it is possible to ensure that the power grid can maintain a stable power supply even in adverse weather and emergencies.